Decisi-o-rama: An open-source Python library for multi-attribute value/utility decision analysis. (January 2021) - Chacon-Hurtado, J.C.; Scholten, L.
Abstract: Environmental decisions are complex as they are multi-dimensional, highly interdisciplinary and not only involve multiple stakeholders with conflicting objectives, but also many possible alternatives with uncertain consequences. The difficulty lies in making trade-offs between tough value trade-offs on the one hand while appreciating uncertain impacts of alternatives on the other. To support decisions tackling such problems, a combination of multi-criteria decision analysis (MCDA) and environmental models is promising yet limited by the available MCDA software. Here, we present Decisi-o-rama, an open-source Python MCDA library for single and sets (portfolios) of alternatives in the context of multi-attribute value/utility theory (MAUT/MAVT). Its development was driven by four aspirations that are crucial for usability in the context of environmental decision-making: (1) interoperability, (2) uncertainty-awareness, (3) computational efficiency, and (4) integration with portfolio decisions. The results indicate that these aspirations are met, thus facilitating the adoption of MCDA methods by environmental researchers and practitioners. Highlights: Decisi-o-rama is an open-source Python library for Multi-Criteria Decision Analysis (MCDA) to support environmental decisions. Decisi-o-rama supports uncertainty-aware MCDA in the context of MAUT/MAVT for single and portfolios of alternatives. Decisi-o-rama allows to quickly run large MCDA problems, supporting on-the-fly model exploration with decision makers. Decisi-o-rama is highly interoperable, allowing flexible use in concert with both simple or complex environmental models.